Apoptotic Cell Clearance in Health and Disease - Amiram Ariel (Frontiers Research Topics, 2018)
Clearance of apoptotic cells is essential for proper development, homeostasis and termination of immune responses in multicellular organisms. Thus, cellular and molecular players taking part in the sequential events of this process are of great interest. Research in the last 20 years has indicated that specific ligands and receptors take part in the attraction of immune cells toward apoptotic targets and in the interactions between apoptotic cells and professional as well as non-professional phagocytes that engulf them. Moreover, phagocytosis of apoptotic cells (efferocytosis) leads to significant phenotypic changes in the engulfing cells suggesting that it is a major fate-determining event for phagocytes. Particularly, efferocytosis has an important impact on the inflammation-resolution axis as well as embryonic development and tissue morphogenesis. Deficiencies in these processes can result in health threats, such as autoimmunity, atherosclerosis, bone loss, obesity, infertility, neurodegeneration, fibrosis and cancer. This eBook brings together 24 original research and review manuscripts that cover various aspects of apoptotic cell removal during normal development and homeostasis as well as in tumorigenesis and regenerative processes following injury.